The Influence of Individual Characteristics on Employee Performance at PT. Cipta Selaras Abadi in Parung-Bogor - Rendy Sapto Ajie; Hadi Supratikta (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of individual characteristics on employee performance at PT. Cipta Selaras Abadi in Parung-Bogor. The method used is explanatory research with a sample of 53 respondents. The analysis technique uses statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study of individual characteristics variables obtained an average score of 3.772 with good criteria. Employee performance variable obtained an average score of 3.896 with good criteria. Individual characteristics have a positive and significant effect on employee performance with a regression equation value of Y = 13,220 + 0.683X, and a correlation coefficient value of 0.801 or has a strong relationship with a determination value of 64.2%. Hypothesis test obtained sig. 0.000 < 0.05.